2013
DOI: 10.4103/1305-7456.110166
|View full text |Cite
|
Sign up to set email alerts
|

Dental subscale of children′s fear survey schedule and dental caries prevalence

Abstract: Objective:To assess the level of fear of dental procedures among 6-12 year school children and correlate the prevalence of dental caries with their dental fears scores.Materials and Methods:The study sample of 444 school children, comprising of 224 girls and 220 boys in the age group of 6-12 years old from a private English medium school were selected. Each student was asked to independently complete a Children's Fear Survey Schedule – Dental Subscale (CFSS-DS) questionnaire. Children having a score of ≥ 38 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…Statistically significant diff erences were found between the two groups of children divided by age and history of dental trauma. Children were shown to be most afraid of injections, dentists, dental examinations, having instruments in their mouth and tooth cleaning 20,21 . In this study, children without trauma expressed the greatest amount of fear, while children with one or repeated trauma had signifi cantly less pronounced fear.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant diff erences were found between the two groups of children divided by age and history of dental trauma. Children were shown to be most afraid of injections, dentists, dental examinations, having instruments in their mouth and tooth cleaning 20,21 . In this study, children without trauma expressed the greatest amount of fear, while children with one or repeated trauma had signifi cantly less pronounced fear.…”
Section: Discussionmentioning
confidence: 99%
“…[262728] Meechan reported that the clinical impact of articaine's higher postinjection pain scores than lignocaine is negligible. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Among common fears, the fear of dentist has been ranked the fourth. (Beena, 2013) It has been found that anxiety varies in content, pattern, and level of fear across different cultures and across different populations. (Armfield et al, 2006) Research indicates the estimated prevalence of dental fear from the lowest level of 3% to the highest level of 43% in different populations.…”
Section: Introductionmentioning
confidence: 99%